Transverse response of pile group foundations supporting a long-span cable-stayed bridge under uniform and nonuniform excitation. Issue 121 (June 2019) - Liang, Fayun; Jia, Yajie; Xie, Wen; Sun, Limin; Chen, Haibing
Abstract: Multiple shaking table tests on an integral long-span cable-stayed bridge model were carried out to study the transverse response of pile group foundations. An elaborate bridge model was fabricated according to an assumed bridge with a total length of 2672 m and a geometric similarity ratio of 1/70. The superstructure of the bridge model consisted of a bridge girder, cables, two transition piers, four auxiliary piers and two pylons. The substructure of the model consisted of eight groups of piles embedded in synthetic soil. Accelerations, displacements and bending moments of the piles that supported the transition piers, auxiliary piers and pylons, respectively, were analyzed when the bridge was excited uniformly and nonuniformly in the transverse direction. The nonuniform excitation test was implemented by inputting the same motion to different shaking tables at different times. Three types of earthquake waves with different predominant frequencies were applied to the integral bridge model from low to high intensity. The test results indicated that distinct differences arose between the motions at the top of the pile groups supporting different parts of the superstructure despite the integral bridge model being subjected to uniform excitation. The large displacement difference between pile groups may be one of the origins of damage or even collapse of the superstructure. The amplification ratio of acceleration at the top of the pile group supporting the transition piers increased when the bridge model was excited by waves of low predominant frequency with increasing intensity. The transfer functions of accelerations (Fourier spectra of output accelerations over that of shaking table accelerations) at the top of the pile groups supporting the auxiliary piers were bimodal, which is different from the results of shaking table tests simulating the superstructure with a single degree of freedom (SDOF) system, in which only unimodal transfer functions can be obtained. The influence of the wave passage effect on the seismic response of the pile groups is detectable when the bridge model is excited longitudinally, while the influence is undetectable when the bridge model is excited transversely. Highlights: An integral bridge model including superstructure and pile groups was fabricated. The acceleration of piles may rise at faster rate with increasing input intensity. Transfer functions of acceleration for pile group under auxiliary piers are bimodal. The motions of pile groups under different parts of the superstructure are different.